Kindergarten Obesity and Academic Achievement: The Mediating Role of Weight Bias - Yu, Baeksan (Frontiers in Psychology, 2021)
This study draws the attention towards the importance of reducing weight discrimination against children for their educational success, as an issue of social justice. We investigate the consequences of early-onset obesity identifying the mediating mechanisms in the relationship between childhood obesity and academic achievement. To do so, we employ the Early Childhood Longitudinal Study-Kindergarten Cohort (kindergarten to fifth grade) in the US (ECLS-K: 2011) and apply a parallel process latent growth model with a combination of quasi-experiments and econometrics. The results of this study suggest that the negative influence of weight stigmatization and discrimination among teachers is small but might be comparable to racial/ethnic discrimination, especially for girls (B=–.09, 95% BC CI [–2.37 to –.46]).